Sustainable usage of demolished concrete waste as a sub-base material in road pavement - Mazhar, Mohd. Aamir; Alam, Pervez; Ahmed, Sirajuddin; Khan, Mohammed Sharib; Adam, Farhan Ali (Frontiers in Sustainability, 2023)
Today, handling and managing the debris left behind after the demolition of concrete structures like recycled concrete aggregate, waste rock, crushed stone aggregate, reclaimed asphalt pavement, crushed clay brick, fine recycled glass, and gravel is a significant challenge for many nations around the world. The demand for a workable and clever use of the waste produced by these substances is growing as time goes on. Since demolished concrete waste must be completely recycled to minimise environmental damage and safeguard natural resources, it is crucial to address this issue locally. Numerous studies reveal that demolished concrete has good strength and can be used as a green material, which will eventually make construction more economical. The objective of this research was to determine the performance and engineering characteristics of demolished concrete waste and to find out if they are suitable for usage in the base and sub-base of road pavements. The new or fresh aggregates were replaced with the demolished concrete waste aggregates in terms of percentage by weight from 0% to 100%. The water absorption rose from 1.58% to 4.65% when fresh aggregates were replaced with demolished concrete waste aggregates, indicating that the water-cement ratio improved. The crushing value also improved from 26.54% to 55.29%, the impact value increased from 27.86% to 58.05%, and the abrasion value increased from 26.96% to 35.58%. The result of this study indicates that a mix of 50% of recycled aggregates and 50% of fresh aggregates can be sustainably used for the sub-base of roads. The reuse of demolished concrete waste as a sub-base material will help in achieving socio-economic and environmental sustainability.